Electrolyte Disturbance and the Type of Malarial Infection - Asima RANI; Shahnaz AKHTAR; Syed Kashif NAWAZ; Shazia IRFAN; Sadia AZAM; Muhammad ARSHAD (Tehran University of Medical Sciences, 2015)
Background: Electrolytes play an important role in the normal functioning of human body. Electrolyte imbalance and mineral disturbances is the common clinical manifestation in several infectious diseases including malaria. Malaria is a mosquito borne serious infectious disease of the world. Plasmodium vivax and P. falciparum are the main agents responsible for malaria in Pakistan. Electrolyte imbalance in malarial infection may lead towards the severity of disease. Methods: The present study analyzed the electrolytes levels (Na, K, Ca and Mg) in malarial patients and healthy individuals. Patients were categorized into two groups, P. falciparum and P. vivax, based on causative species of Plasmodium. Study consisted of 173 individuals, out of which 73 were malarial patients and 100 were normal healthy individuals. Results: Concentrations of Na, K, and Ca were low in the blood of malarial patients as compared to healthy individuals (P<0.05). No significant difference for these electrolytes exists between P. falciparum and P. vivax infected groups (P>0.05). The concentration of Mg was changed based on exposure to the type of parasite. In P. falciparum infection, the level of Mg was lower than healthy individuals was (P<0.05). Discordantly, in case of P. vivaxinfection, Mg level was higher than healthy individuals were (P<0.05). No variation was noticed in electrolytes levels due to gender differences (P>0.05). Conclusion: Variation in Mg levels occurs due to exposure of Plasmodium depending on its type. The levels of Na, K and Ca are also changed due to Plasmodium, regardless of its type.   Keywords: Malaria, Electrolytes, Plasmodium falciparum, Plasmodium vivax